Synthesis and mechanistic studies into the cytotoxic activity of garlic-related trisulfides in cancer cells - Ali, Doaa (Department of Chemistry, 2025)
Garlic has long been recognized for its medicinal properties and is well-documented to produce organosulfur compounds (OSCs) with significant chemopreventive and therapeutic potential. Among these, trisulfides are notable phytochemicals that exhibit a broad range of biological activities, including anticancer effects both in vitro and in vivo, as well as antimicrobial, antioxidant, and antithrombotic properties. Recent methodologies have enabled the development of novel synthetic methodologies for synthesizing unsymmetrical organotrisulfides. This thesis explores our contributions to the synthesis of these compounds, their cytotoxicity and their mechanisms of action against cancer cells. Building on our group's previous research on the cytotoxicity of ajoene, which demonstrated its ability to modify proteins by S-thioallylation of cysteine residues through a thiol-disulfide exchange reaction, we extend these findings to trisulfides, providing new insights into their potential as anticancer agents. Chapter One offers an overview of naturally occurring trisulfides, highlighting their significant biological activities. It emphasizes trisulfides from natural sources, particularly diallyl trisulfide (DATS), a garlic-derived compound with notable anticancer potential. This chapter sets the stage for exploring trisulfides therapeutic potential in cancer treatment, a central theme of this dissertation. Chapter Two reviews existing synthetic methods for trisulfide formation, highlighting the need for greener and more sustainable approaches. It discusses current challenges, including the difficulty of synthesizing unsymmetrical trisulfides, and introduces our novel method for achieving these compounds with high yield, purity, and selectivity. This chapter lays the groundwork for the synthetic developments detailed in chapter 4. Chapter Three shifts the focus to the cancer biology of organosulfur compounds (OSCs), with a detailed examination of trisulfides. It provides an in-depth analysis of their extraction, biosynthesis, metabolism, and bioavailability, particularly in relation to cancer chemoprevention. The chapter investigates the role of reactive species, including hydrogen sulfide (H₂S) and perthiols (RSSH), generated through thiolysis exchange of trisulfides with protein thiols. The role of H₂S as a crucial gaseous signaling molecule is examined, highlighting its involvement in various physiological processes. The chapter also explores perthiols, Page | IV characterized by their unique chemical properties, which enable them to participate in redox reactions and radical processes. Chapter Four presents our novel methodology for synthesizing unsymmetrical trisulfides, including details of the optimization conditions and the stability of the products. The methodology yields aliphatic trisulfides in high yield and purity, while aromatic trisulfides are more labile. The trisulfide's distinct chemical shifts in 1H NMR allow for their identification and differentiation from other sulfur species. The applicability of this method extends to a range of functional groups, including those derived from cysteine and sugar moieties. Chapter Five investigates the cytotoxic effects of trisulfides in cancer cells, focusing on a refined library of trisulfides to identify structure-activity relationships, particularly in benzyl derivatives. The chapter examines the impact of various substituents on perthiol stability, demonstrating that electron-donating groups prolong perthiol lifetime and enhance cytotoxicity. This by raising their pKa and reducing their disproportionation to homotrisulfides. The p-OMe derivative, in particular, displayed higher extracellular perthiol concentrations, as measured by Ellman's assay, corroborating initial stability studies. The chapter further extends to monitoring H₂S production in WHCO1 cancer cells using a fluorescent probe, establishing that fluorescence intensity, indicative of H₂S concentration, increases with greater electron release from para-substituents. This relationship between enhanced perthiol stability and increased H₂S production reinforces the thiolysis-based mechanism of trisulfide cytotoxicity and suggests a pathway for designing more effective anticancer agents. Additionally, studies using a dansyl-propyl trisulfide probe indicated localisation in the endoplasmic reticulum (ER), suggesting a role for the unfolded protein response (UPR) in conjunction with H₂S signaling in promoting apoptosis.